The role of physiotherapy in promotion of physical activity during the COVID-19 - Juwita, Citra Puspa (International Journal Of Community Medicine And Public Health, 2022)
Background: Physical activity is the right therapy in minimizing the incidence of non-communicable diseases in the community. Physiotherapy has a role in improving body function and movement, one of which is by using physical activity therapy. This study wanted to know the role of physiotherapy in promoting physical activity during the COVID-19 pandemic. Methods: The research design is descriptive quantitative using a questionnaire in order to collect data. The questionnaire consists of 12 statements with Likert scale answers. A total of 42 physiotherapists were selected by simple random sampling spread across developing provinces in Indonesia. Results: During the COVID-19 pandemic, 84% of physiotherapists continued to serve patients, even almost every day. Promotion of physical activity by physiotherapy is better during the COVID-19 pandemic than before the pandemic. The 97% of physiotherapists agreed to promote physical activity. The 66% physiotherapists believe that patients can be motivated to do physical activity if given recommendations by physiotherapists. As many as 79% of physiotherapists have time to provide promotions to their patients. Physiotherapists also stated that 45% of health workers know about physical activity and 66% of physiotherapists believe that clients/patients will do physical activity if recommended by them. Conclusions: It is a necessity for Physiotherapists to always promote physical activity to clients/patients and the wider community.